Occupational Health and Safety (OHS) Risk Analysis Using Fishbone Diagram and Job Safety Analysis (JSA): A Case Study of Spray Booth and Oven Operations in the Automotive Engineering Laboratory of Universitas Negeri Makassar - Muh.Bhilal Halim; Fauziah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Occupational Safety and Health (OSH) in vocational laboratories is critical due to high-risk activities such as spray painting and oven drying involving chemical exposure, heat, and fire hazards. This study aims to analyze OSH risks in spray booth and oven operations at the Automotive Engineering Laboratory of Universitas Negeri Makassar using Job Safety Analysis (JSA) and Fishbone Diagram methods. A mixed descriptive approach was applied through observation, interviews with 15 respondents, and documentation review. Risk assessment was conducted using a risk matrix (likelihood × severity), followed by root cause analysis. The results show that the highest risk level occurs in spray painting activities with a score of R=16 (high risk), mainly due to VOC exposure. Most hazards are categorized as moderate risk (R=10–12), while low risk is R=9. Compliance with personal protective equipment usage is only 70%, indicating behavioral safety gaps. Fishbone analysis reveals that human and environmental factors are the dominant causes of risk. The integration of JSA and Fishbone provides comprehensive hazard identification and root cause analysis. These findings highlight that 60% of risks are moderate, 20% high, and 20% low, emphasizing the urgency of strengthening OSH systems in laboratory environments to prevent occupational accidents effectively.